Meningkatkan Kinerja Guru melalui Kepemimpinan Kepala Madrasah dan Supervisi Pendidikan - Sri Susmiyati; Zurqoni Zurqoni (FENOMENA, 2020)
The research based on the phenomenon that indicates Madrasah Tsanawiyah’s  teachers in Samarinda has a good performance when their headmaster lead them effectively and supervision of functional agencies. The purpose of this research are: (a) to describe the quality of the leadership of headmasters of Madrasah Tsanawiyah, (b) to describe   the quality of educational supervision of Madrasah Tsanawiyah, (c) to describe the quality of the teachers performance of Madrasah Tsanawiyah, (d) to find out the influence of  headmasters’ leadership  on the teachers performance of Madrasah Tsanawiyah partially, (e) to find out the influence of education supervision on the teachers performance of Madrasah Tsanawiyah partially, and (f) to find out the influence of headmasters’ leadership  and education supervision on the teachers performance of Madrasah Tsanawiyah  in Samarinda simultaneously. The entire study population Madrasah Tsanawiyah teachers of Samarinda amount  629 people, while the sample are 76 teachers  applied multi - stage sampling technique. Determination of madrasah through purposive sampling technique, whereas the selection of respondents conducted through random sampling technique. Data collection used questionnaire techniques, while the data analysis techniques used Multiple Linier Regression Analysis. The result of this research concluded as follows. The headmasters’ leadership based teachers’ assessment are categorized as good (μ= 4,09), while the implementation of education supervision are in good category (μ = 3,92), and the teachers’ performance  are in good category (μ = 4,01). Partial leadership has a strong influence on the teachers’ performance of Madrasah Tsanawiyah (r= 0.73). The headmasters’ leadership contributed 54.6 % to the effect for improving the quality of teachers performance. Partial implementation of educational supervision has a strong influence on the teacher performance of Madrasah Tsanawiyah (r = 0.72). Implementation of educational supervision contributed 53% to the effect  for improving the quality of teacher performance. Headmasters’ leadership and implementation of educational supervision simultaneously have a strong influence on the teachers performance of Madrasah Tsanawiyah  (r = 0.74). Headmasters’ leadership and implementation of educational supervision contributied  56.1 % for improving  the quality of teacher performance.